The Achievement Emotions Questionnaire : Validation for pre-adolescent students - Peixoto, Francisco José Brito (2015)
The Achievement Emotions Questionnaire (AEQ) is a self-report instrument developed to measure the emotions of students in academic situations. The main purpose of this research was to adapt and validate this questionnaire to assess preadolescents’ class- and test-related emotions towards mathematics. The participants were 1515 Portuguese students from grades 5 and 7 (age range 10 – 13 years). Confirmatory factor analyses and descriptive statistics confirm the reliability and internal validity of the AEQ for Pre-Adolescents (AEQ-PA), providing evidence that the AEQ-PA is an effective instrument to assess pre-adolescent achievement emotions towards mathematics classes and tests.